A randomized controlled trial of povidone-iodine/dexamethasone ophthalmic suspension for acute viral conjunctivitis - Pepose JS (Dove Medical Press, 2019)
Jay S Pepose,1,2 Abhijit Narvekar,3 Wenlei Liu,4 Reza Haque3 1Pepose Vision Institute, Chesterfield, MO, USA; 2Department of Ophthalmology and Visual Sciences, Washington University School of Medicine, St Louis, MO, USA; 3Ophthalmics, Shire, A Takeda Company, Lexington, MA, USA; 4Biostatistics and Programming, Shire, A Takeda Company, Lexington, MA, USA Purpose: To evaluate the clinical safety and efficacy of povidone-iodine (PVP-I) 0.6%/dexamethasone (DEX) 0.1% ophthalmic suspension vs vehicle in patients with clinically suspected acute viral conjunctivitis. Patients and methods: This was a randomized, double-masked, parallel-group, vehicle-controlled study. Adults with a clinical diagnosis of suspected acute viral conjunctivitis were randomized 1:1 to PVP-I/DEX ophthalmic suspension or vehicle bilaterally four times daily for 5 days (Days 1–5). Evaluation was on Days 1, 3 (+1-day window), and 6 (+1). Patients with signs of acute viral conjunctivitis at the Day 6 visit received open-label PVP-I/DEX for five additional days and were evaluated on Day 11–14. The primary efficacy endpoint was clinical resolution of acute viral conjunctivitis in the study eye at the Day 6 visit. Results: Overall, 132 patients were randomized and received treatment (PVP-I/DEX, n=66; vehicle, n=66); 38 patients continued into the open-label portion of the study. Not enough patients with confirmed adenoviral conjunctivitis (n=32/132) were enrolled to assess the primary endpoint, although there were some efficacy trends in the PVP-I/DEX group for global clinical score (sum of watery conjunctival discharge and bulbar conjunctival redness). There were no serious treatment-emergent adverse events (TEAEs) and no patients discontinued due to a TEAE. In the masked phase, 56.1% of patients receiving PVP-I/DEX experienced at least one TEAE vs 43.9% in the vehicle group; 78.9% of patients in the open-label phase experienced at least one TEAE. Most TEAEs were mild in severity. Conclusion: PVP-I/DEX ophthalmic suspension administered for ≤14 days had a favorable safety profile and was generally well tolerated. Keywords: adenoviral conjunctivitis, dexamethasone, povidone-iodine, randomized controlled trial